Effectiveness of Reward and Punishment Systems in Enhancing Employee Motivation and Performance: A Human Resource Management Case Study at Medika Clinic, Lelilef Village, North Maluku, Indonesia - Muhammad Qussayn; Abdullah W. Jabid; Johan Fahri; Putri Ayunnisa Sukur (Journal of International Conference Proceedings, 2025)
This study explores the effectiveness of the reward and punishment system at Medika Pratama Perkasa Clinic, a private healthcare facility located in the remote mining area of Lelilef Village, Central Halmahera, North Maluku. Operating with limited human resources and high workloads, the clinic applies a qualitative exploratory case study approach, using interviews, observations, and document analysis, validated through source and method triangulation. The findings show that rewards—such as financial incentives, certificates, additional leave, and training—positively improve staff motivation and loyalty. Meanwhile, punishments including verbal and written warnings and incentive reductions help enforce discipline, although they generate psychological pressure for some employees. The remote context intensifies challenges related to limited facilities, referral constraints, and stressful work conditions. The study concludes that the system works adequately but requires greater consistency, clearer criteria, and stronger non-financial support through mentoring and coaching. These results contribute to understanding human resource management in healthcare organizations operating in remote areas